Prospective Associations Between Salivary Biomarkers of Inflammation and Body Mass Index in Adolescents - Keri M. Kemp; Catheryn A. Orihuela; Douglas A. Granger; Retta R. Evans; Sylvie Mrug (Obesity Science & Practice)
ABSTRACT Background Childhood and adolescent obesity, which affects nearly 1 in 5 youth in the US, presents a pressing public health concern. Obesity is linked to chronic low‐grade inflammation, which exacerbates comorbidities. Noninvasive tools are needed to monitor obesity‐related inflammation and assess weight‐management interventions in children and adolescents. Objective This study investigated the associations between Body Mass Index z‐score (BMIz) and salivary biomarkers: C‐reactive protein (CRP), cytokines interleukin (IL)‐1β, IL‐6, IL‐8, and tumor necrosis factor (TNF)‐α. Methods A sample of 280 adolescents (Mage = 12.1 years, SD = 0.44) was followed for 2 years (3 time points) from 2019 to 2021. An autoregressive cross‐lagged path model was used to examine the prospective relationships between BMIz and salivary biomarkers. Results Findings indicated a bidirectional relationship between BMIz and salivary CRP levels, suggesting a feed‐forward cycle in which excessive weight gain and inflammation mutually amplify each other. Salivary cytokines were not associated with BMIz. Conclusions This study underscores the utility of salivary CRP as a noninvasive biomarker for obesity‐related inflammation. Monitoring salivary CRP levels could aid in targeting interventions to prevent obesity‐related complications early in life.